Bibliometric Analysis: The Role of ESG in Green Finance - Azam Asykarulloh; Muh Syaiful Bakhri; Muhammad Isbad Addainuri; Askal Samiudin (Jurnal Magister Ekonomi Syariah, 2025)
This study aims to conduct a comprehensive bibliometric analysis of the development of the Environmental, Social, and Governance (ESG) and green finance literature. Research data was obtained from 519 scientific articles indexed in the Scopus database in the period 2020–2025. The analysis was carried out using a bibliometric approach through Bibliometrix and Biblioshiny software to map the performance of publications, topic evolution, conceptual structure, and research collaboration patterns globally. The results show that ESG and green finance related publications are experiencing exponential growth, which indicates that this field is a rapidly growing emerging research front. The thematic evolution analysis indicates a shift in research focus from normative issues and regulatory frameworks to more implementive and performance-based studies, especially related to ESG performance and green finance instruments. Thematic mapping places green finance, sustainable development, and ESG performance as the underlying themes that underpin the literature, while general concepts such as ESG and sustainable finance show a tendency towards specialization or conceptual saturation. Analysis of global collaborations shows a strong geographical concentration of research, with China emerging as the dominant actor in international research networks. This research contributes by uncovering the phenomenon of publication inflation and the citation age effect, identifying potential geographical bias in the ESG and green finance literature, and proposing a policy-market integration perspective as a conceptual framework to bridge the fragmentation between regulation-based approaches and financial markets. These findings provide important implications for the development of research agendas, evidence-based policy formulation, and sustainable investment strategies.